Functional outcome of surgical management of tibial plateau fractures in adults - Swarup, Arunim; Rastogi, Avinash; Singh, Siddharth; Swarn, Kamal (International Journal of Research in Medical Sciences, 2016)
Background: Tibial plateau fractures are one of the commonest intra articular fractures. These injuries encompass many varied fracture configuration that involve medial, lateral or both tibial plateau with varied degree of compression and articular displacements. Being one of the major weight bearing joints of the body, these fractures are of paramount importance. Since there are various modalities for fixation of these fractures with satisfactory results, but there is no general consensus as to which modality is the best in terms of functional outcome and proving the superiority of one over the other. Keeping this aim in mind, we have conducted the present study to determine the efficacy of different practised methods of fixation, and if one are superior to the other. Methods: Sixty cases of tibial plateau fractures were treated with various surgical modalities and were followed up for a period of 2 years (2013 to 2015) at N.S.C.B Subharti hospital and their functional outcome was evaluated using Rasmussen’s functional score. Results: On selection these patients were classified according to Schatzker classification and were fixed accordingly using percutaneous cannulated cancellous screw, plating using LCP/ buttressing by open or MIPPO technique and screws depending upon the fracture configuration. Early range of motion was started as soon as pain subsided and weight bearing was deferred until radiological signs of union were evident. The knee range of motion was excellent to very good and weight bearing after complete union was satisfactory. Infection and stiffness in 2 cases was seen and there was one case of non-union in this series. Conclusions: Surgical management of tibial condylar fracture will give excellent anatomical reduction and rigid fixation to restore anatomical congruity, facilitate early motion, hence to achieve optimal knee function and reducing post traumatic osteo-arthritis.